Fluorescence Properties of Flavin Semiquinone Radicals in Nitronate Monooxygenase. (20th May 2019) - Su, Dan; Kabir, Mohammad Pabel; Orozco‐Gonzalez, Yoelvis; Gozem, Samer; Gadda, Giovanni
Abstract: Fluorescent cofactors like flavins can be exploited to probe their local environment with spatial and temporal resolution. Although the fluorescence properties of the oxidized and two‐electron‐reduced states of flavins have been studied extensively, this is not the case for the one‐electron‐reduced state. Both the neutral and anionic semiquinones have proven particularly challenging to examine, as they are unstable in solution and are transient, short‐lived species in many catalytic cycles. Here, we report that the nitronate monooxygenase (NMO) from Pseudomonas aeruginosa PAO1 is capable of stabilizing both semiquinone forms anaerobically for hours, thus enabling us to study their spectroscopy in a constant protein environment. We found that in the active site of NMO, the anionic semiquinone exhibits no fluorescence, whereas the neutral semiquinone radical shows a relatively strong fluorescence, with a behavior that violates the Kasha–Vavilov rule. These fluorescence properties are discussed in the context of time‐dependent density functional theory calculations, which reveal low‐lying dark states in both systems. Abstract : As one of only a few fluorescent radical species, FMNH . in nitronate monooxygenase has a sharp band in the excitation spectrum instead of mimicking the general shape of its UV–visible absorption spectrum; this violates the Kasha–Vavilov rule. TD‐DFT calculations reveal a low‐lying noπ* dark state (D2 ) that casts light on the unusual fluorescence of a radical.